Peningkatan Kesadaran Pengelolaan Sampah dan Optimalisasi Digital untuk UMKM di Kelurahan Tonja, Kecamatan Denpasar Utara, Kota Denpasar - Cokorda Krisna Yudha; Ni Luh Putu Indiani (Community Service Journal (CSJ), 2024)
Tonja Village is one of the sub-districts located in North Denpasar District, Denpasar City, Bali. Tonja Village has strong economic potential, especially through the trade sector. The large number of residents involved in trade creates opportunities for the development of small and medium enterprises (SMEs) as well as improving the local economy. Of the various challenges identified, the two main problems that were the focus of the intervention were the lack of public awareness about good waste management and the difficulties experienced by Micro, Small and Medium Enterprises (MSMEs) in understanding and optimizing the use of digital platforms. The "Zero Waste, Full Impact: Towards a Waste-Free Life" program is designed to increase public awareness and participation in good waste management through door-to-door outreach and waste management training. As a result, there has been a significant increase in community participation in the waste bank program, which has had a positive impact on the environment and local economy. The second program, "Digital Optimization: Digital Marketing, Digital Bookkeeping, and Tax Rules for MSMEs and Cooperatives," aims to improve the skills of MSME players in using digital technology for marketing and bookkeeping. This training succeeded in increasing participants' understanding of digital marketing, digital bookkeeping and tax regulations, which enabled MSMEs to be more competitive in the digital market. The conclusions from this program show that participatory approaches and direct education are effective in overcoming local problems. This program also provides recommendations for further replication and development, including the importance of ongoing mentoring and expanding the program to other regions. It is hoped that the results of this program can become a model for similar efforts to improve the quality of life of the community and develop the local economy.